Genetic diversity of physical, nutritional and functional properties of cowpea grain and relationships among the traits - Muranaka, S.; Shono, M.; Myoda, T.; Takeuchi, J.; Franco, J.; Nakazawa, Y.; Boukar, O.; Takagi, H. (Cambridge University Press, 2016)
Cowpea is traditionally important as an affordable source of protein and minerals and of cash income in sub-Saharan Africa, especially for small-scale farmers who have limited options for food and cash crops. The development and deployment of cowpea varieties with improved nutrition and quality that meet the needs of farmers and consumers should enhance cowpea consumption and production in the region. We have identified genetic diversity in various grain quality-related traits of cowpea and relationships among the traits. Wide genetic variation and strong correlations among crude protein, Fe and Zn contents suggest the possibility of improving the concentrations of these nutritional factors simultaneously. Low associations among physical and nutritional properties of grain indicate the possibility of introgressing favorable traits utilizing identified genetic resources. However, narrow variation in amino acid (AA) composition suggests a lesser possibility of improving the contents of specific AAs in cowpea, but it gave a reliable nitrogen-to-protein conversion factor of 5.45 for the estimation of crude protein content. Several improved breeding lines were identified with low concentrations of flatulence-causing oligosaccharides and various favorable agronomic traits and nutrient contents. TVu-12802 had the highest contents of crude protein and high contents of micronutrients, with a low ratio of phytic acid to Fe and Zn contents.